Apremilast: a PDE4 inhibitor for the treatment of psoriatic arthritis. (May 2015) - Abdulrahim, Hunar; Thistleton, Samuel; Adebajo, Adewale O; Shaw, Tim; Edwards, Christopher; Wells, Alvin
<x xml:space="preserve">Abstract</x> Introduction: The evidence base for disease-modifying anti-rheumatic drugs used in psoriatic arthritis (PsA) is surprisingly weak, with most having little robust evidence to support their clinical use. Furthermore, there remain safety and tolerability concerns with both these and more recently available biological therapies. <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Apremilast&logicalOpe1=OR&field2=articletitle&text2=Apremilast&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Apremilast, a novel, small molecule, represents the first oral therapy specifically developed for PsA. Areas covered: This review describes the pharmacokinetic properties of apremilast and available data demonstrating significant benefits to both clinical and histological features of inflammatory arthritis. The key findings from a large Phase III clinical program will also be discussed, including short- and long-term efficacy outcomes and, importantly, the safety profile. Indications other than PsA will also be briefly reviewed. Given the recent nature of much of the data, published literature as well as information available only in the abstract format are included in this review. Expert opinion: Studies show that treatment with apremilast results in significant improvement in both skin psoriasis and PsA symptoms. Apremilast has been approved by both the United States FDA and European Medicines Agency for treatment of PsA. Use of this medication is recommended in active PsA patients, according to local licensing.